Health Program Management Factors Related to Budget Realization at the Kolaka District Health Office - muhammad ikhsan akbar; Sartini Risky; La Ode Saafi; Andi Asri (Public Health of Indonesia)
Objective: The purpose of this study was to analyze the Health Program Management Factors Associated with Budget Realization at the Kolaka District Health Office.